EVALUACIÓN DEL CMC Y GOMA XANTHAN EN LA ELABORACIÓN DE NÉCTAR DE NARANJA (Citrus sinensis) CON REMOLACHA (Beta vulgaris) - LAVAYEN CASTRO, NOHELIA MARIBEL (2025)
This research was carried out in the agro-food laboratory located at the “La María” Campus of the UTEQ (Cantón Mocache - Recinto San Felipe, Km 7 ½ via Quevedo - el Empalme, in the canton of Mocache in the Province of Los Ríos), with the objective of evaluating CMC and Goma Xanthan in the preparation of orange nectar (Citrus sinensis) with beet (Beta vulgaris), a complete randomized design with factorial arrangement of A*B with 6 treatments and 4 replicates was carried out, where factor A had 3 levels and factor B had 2 levels, physicochemical, sensory and microbiological characteristics